Perbandingan Aktivitas Antioksidan Pada Ekstrak Serta Krim Kobinasi Ekstrak Jeruk Nipis (Citrus Aurantifolia) Dan Daun The Hijau (Camellia Sinensis) Untuk Treatment Striae Gravidarum - Rahman, Alief Putriana (School of Pharmacy Institut Teknologi Bandung, 2024)
Striae Gravidarum (SG) are stretch marks seen in pregnant and postpartum women. Treatments for SG aim to reduce redness and enhance pigmentation and collagen. Chemical peeling treatment can be harmful. They may cause liver, kidney, and skin issues, including inflammation and skin loss. Meanwhile, laser treatments may lead to skin inflammation for 2-4 days post-procedure. Despite this, they remain popular. Topical retinoic acid can cause birth defects and miscarriages if used in pregnancy. This highlights the need for natural treatments for SG. This study aimed to find the content and the antioxidant activity of lime peel extract, green tea, and cream combination both of extract. Besides, another goal was to determine physical characteristics formulation in the cream preparation. Method of this research is phytochemical screening for extract. Measure Vitamin C, EGCG and antioxidant activity using UV-Vis spectrophotometry. The cream contains 10% lime and 6% green tea extracts. This study found lime peel and green tea extracts each yielded less than 10%. Phytochemical tests revealed lime extract has alkaloid, Steroid, Saponin, Flavonoids, Tannins, and Antraquinone. Lime peel extract has vitamin C 16,56103 mg/100 mg of extract. Green tea extract contains EGCG 22,5114 mg/100 mg of extract. Lime peel extract's antioxidant activity is 268,3130 ppm. For green tea, it's 154,4009 ppm . The combination cream has 115,7629 ppm of antioxidant activity. Its physical properties meet good cream standards. The conclution of this research is combination cream of lime peel and green tea extract has the highest antioxidant activity